2019
DOI: 10.1159/000495885
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Uremic Toxin Indoxyl Sulfate-Induced Osteoblastic Calcification by SET Domain Containing Lysine Methyltransferase 7/9 Protein

Abstract: Background: Vascular calcification (VC) is a very common phenomenon in patients with chronic kidney disease (CKD). It has been reported that some histone methylation play a role in VC as an epigenetic regulator. Indoxyl sulfate (IS) is a protein-bound uremic toxin that has been proven as one of the major risk factors of cardiovascular disease in CKD. SET domain containing lysine methyltransferase 7/9 (SET7/9) is one of the important histone methyltransferases. Objectives: This study aimed to determine the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…It is well known that the uremic toxins accumulated in the serum and contributed to the cardiovascular events in CKD patients. IS, one of the most important uremic toxins that have profound effects on endothelial dysfunction and VC (Chen et al, ; Shang et al, ). It has been reported that IS stimulation promotes phenotypic switch of VSMCs from a contractile phenotype to an osteogenic phenotype (Muteliefu, Enomoto, Jiang, Takahashi, & Niwa, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the uremic toxins accumulated in the serum and contributed to the cardiovascular events in CKD patients. IS, one of the most important uremic toxins that have profound effects on endothelial dysfunction and VC (Chen et al, ; Shang et al, ). It has been reported that IS stimulation promotes phenotypic switch of VSMCs from a contractile phenotype to an osteogenic phenotype (Muteliefu, Enomoto, Jiang, Takahashi, & Niwa, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…LSD1 and G9a could promote HIF1α expression and increase its stability, which subsequently accelerates VEGFA and its downstream genes expression, and activates VEGFA signaling pathway to regulate tumor angiogenesis. In addition, EZH2, DOT1L, SMYD3, SETD3 and SET7 are also involved in regulating VEGFA expression or VEGFA signaling pathway during tumor angiogenesis downregulation of the expression of histone methyltransferase Set7/9 and with autophagy activation, which indicates that Set7/9 downregulation and autophagy activation may be the key mechanisms of indoxyl sulfate-induced vascular calcification in chronic kidney disease [133]. Intercellular adhesion molecule 1 (Icam1) mediates the adhesion and transmigration of leukocytes across the endothelium to promote inflammation in the vasculature.…”
Section: Histone Methylation In Other Forms Of Vasculopathymentioning
confidence: 99%
“…After screening through 224 articles, we identified 66 original reports examining epigenetic processes in VC ( Figure 1). Interestingly, most reports (n = 40; 60.6%) looked into the pathogenic role of non-coding RNA in VC, while histone modification (n = 6; 9.1%) [53][54][55][56][57][58], DNA methylation (n = 8; 12.1%) [5,[59][60][61][62][63][64][65], and chromatin changes (n = 3; 4.5%) [66][67][68] accounted for one-fourth only. Nine (13.6%) [69][70][71][72][73][74][75][76][77] examined the discrepancy of epigenetic signatures between subjects or animals with and without VC but not their pathogenic influences.…”
Section: Strategy Of Literature Review and Findingsmentioning
confidence: 99%
“…Kurozumi et al examined an in vitro model of interleukin-6 (IL-6)-induced VSMC calcification, and discovered that JMJD 2B, a histone lysine demethylase, modulated the expression of RUNX2 through a transcriptional repressor, H3K9me3, and a transcriptional enhancer, H3K4me3, located in the RUNX2 promoter region [57]. Chen et al, alternatively, disclosed that down-regulation of lysine methyltransferase 7/9 (SET7/9) played a role in another model of IS-induced VSMC calcification [58]. However, the exact methylation signature in the IS model was not described clearly in their findings.…”
Section: Histone Modification In Vcmentioning
confidence: 99%